Процеси та алгоритми комутації у силових трансформаторно-ключових вузлах - Липківський, К.О.; Халіков, В.А. (Технічна електродинаміка, 2012)
Transient processes appearing on switching of the winding of transformer are considered, including in consequence of saturation core. Visual modeling of transient processes is done with MATLAB and techniques for minimization or elimination of transients are suggested.